Incidence and indications of peripartum hysterectomy among patients admitted in Dhaka medical college hospital - Afroz, Rumana; Dewan, Farhana; Sarker, Manjuman Ara; Ara, Rifat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Peripartum hysterectomy is a mutilating surgery in obstetrics. Peripartum hysterectomy remains one of the important procedures to reduce maternal mortality and morbidity in Bangladsh. The study aimed to determine the incidences of peripartum hysterectomy in patients admitted to Dhaka medical college hospital (DMCH) by thorough evaluation of cases. Methods: This was a cross-sectional clinical study carried out in the department of obstetrics and gynaecology, DMCH. The duration of the study was one year, from July 2008 to June 2009. About 42 patients with peripartum hysterectomy took part in it. All patients who underwent peripartum hysterectomy with no other chronic illness, matched with age criteria, and gave consent were among the inclusion criteria. Data were collected and analyzed with the software SPSS. Results: Incidence of 6.25 per 1000 deliveries. Majority age group 29-34 years (38.09%). P/V bleeding with shock (23.81%), P/V bleeding without shock (35.71%), term pregnancy with labor pain (21.43%), and ruptured uterus (19.05%). The primary indication was uterine rupture (57.14%), followed by postpartum hemorrhage (26.19%) and sepsis (4.76%). Subtotal hysterectomy was performed in 88.09% of cases. Intraoperative complications included severe hemorrhage (23.81%) and urinary bladder injury (14.28%). Postoperative complications included febrile morbidity (42.85%), wound infection (23.81%), and paralytic ileus (28.57%). Maternal mortality was 16.67%, and perinatal outcomes included 61.9% stillbirths, 9.52% early perinatal deaths, 4.76% requiring ICU support, and 28.57% alive. Conclusions: Through effective antenatal care, reduced primary cesarean section rate, identification of patients at risk, enhancement of blood transfusion facilities, together with improvement of surgical skills the morbidity associated with the operation and mortality rate can be reduced.